AN IMPACT OF CONSUMER SHOPPING STYLES IN SHOPPING MALLS OVER PURCHASE BEHAVIOR WITH REFERECNE TO CHENNAI CITY - Mr. G. Aravindhan, Dr. R. Satish (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
This research is to analyse how shopping is done in shopping malls of Chennai. The growth of Indian Retail Industry is showing how people are changing their styles while shopping in various malls of Chennai. The growth of malls is a clear indication of organized retail stores in Chennai and India as well. Usage of smart phones and Internet penetration in India is growing at a faster rate and it leads to more footfalls in the shopping malls. Recent changes of FDI policies in Indian Retail Industry are a great boost to the shopping malls. The objective of the study is to find out important shopping styles carried out by the Chennai consumers in various shopping malls. By using SEM analysis, the researcher found major shopping styles which have an impact on purchase behaviour.